INTENSIDADE DAS PARTIDAS DE FUTEBOL FEMININO UNIVERSITÁRIO NA DIVISÃO I DA NCAA DURANTE UMA TEMPORADA COMPETITIVA - SOUSA, Victor Geovani Soares de (2021)
Objective: The purpose was to evaluate the intensity of university women's soccer matches in Division I of the NCAA during a competitive season. Materials and methods: the sample consisted of 18 players competing in Division I of the NCAA. A total of 13 games were analyzed during the regular competitive season. Data on average intensity, accumulated time by HR zone, behavior FC throughout the match and in home and away situations were collected for each match. The HR zones adopted were: Z1 = 50-59%, Z2 = 60-69%, Z3 = 70-79%, Z4 = 80-89% and Z5 = 90-100% of the maximum HR. For comparisons throughout the games, by time range and HR zone, a one-way ANOVA with repeated measures was performed. In the comparisons of average intensity of each match, high intensity zones (Z4 and Z5) and low intensity zones (Z1, Z2 and Z3) between first and second time, two-way ANOVA with repeated measures was used. When necessary, Tukey's post hoc was used. A level of statistical significance of p <0.05 was adopted. Results: the average intensity of the 13 games evaluated was 89% of the HR max. It was also observed that the players accumulated more time in zones Z5 and Z4 compared to zones Z3, Z2 and Z1. In the comparison of intensity between first and second half, home matches vs. outside and time bands every 15 minutes, no significant differences were found. Conclusion: the intensity of NCAA women's college soccer matches in Division I was high and steady throughout the 90 minutes of the game, as well as during all games of the season.